KEARIFAN LOKAL MASYARAKAT ADAT DALAM MENJAGA KETAHANAN PANGAN MELALUI TRADISI REWA`NG PLEA “(Studi Kasus Desa di Daniwato Kecamatan Solor Barat Kabupaten Flores Timur)” - Antonio Jawan Jawan; Frans Bapa Tokan; Didimus Dedi Dhosa (Journal Education and Government Wiyata, 2025)
This study is entitled "Local Wisdom of Indigenous Peoples in Maintaining Food Security Through the Rewa`Ng Plea Tradition" (Case Study of Villages in Daniwato, West Solor District, East Flores Regency). To explain the main problem in the title above, a theory is built on local wisdom and food security with a focus on local wisdom in implementing the rewang p'lea tradition ceremony based on aspects of the stages of implementing the rewang p'lea tradition and local wisdom in maintaining food security. The method used in this study is a qualitative descriptive method and the techniques used are interview techniques, observation, and documentation. The results of the study show that (1) this tradition begins with the initial stage of implementation involving the preparation of natural ingredients consisting of crushed tree trunks and dog blood and liver. This process not only involves practical knowledge in utilizing nature, but also contains spiritual values that have been passed down from generation to generation. Thus, the community prepares this potion to be used to protect their gardens from pests that can damage agricultural products, such as caterpillars and grasshoppers. (2) The implementation stage of the rewang p’lea ritual involves the entire community involved in this traditional ceremony, both from the men who play an important role in the ritual procession, as well as the general public (ribu ratu). In this process, the traditional potion that has been prepared is then distributed to all members of the community, who then place the potion at strategic points in their gardens. (3) In the final stage of implementation, the Daniwato Village community follows the taboo of not entering the garden for three days after the ritual is carried out, as a form of respect for the spiritual power that has been applied to their gardens. This taboo shows how the rewang p’lea ritual is viewed as something sacred and requires patience and caution so that the success of the ritual can be realized. (4) The rewang p’lea tradition in Daniwato Village is a real example of how the local wisdom of indigenous communities in maintaining food security is rooted in very deep and meaningful cultural values. Through close cooperation between residents, the use of natural materials, and appreciation of spiritual and social values, the community is able to maintain the continuity of their agricultural production despite facing the threat of pests.